ANALISIS PENGAJUAN KLAIM BPJS KESEHATAN NON KAPITASI PUSKESMAS NANGGULAN KABUPATEN KULON PROGO - Heri Kusniawan; Harinto Nur Seha; I Gusti Agung Ngurah Putra Pradnyantara (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2021)
The Nanggulan Community Health Center is the main accredited health center, it is known that 23,000 residents of the Nanggulan sub-district are registered as members of the BPJS Health, both PBI and non-PBI. In the non-capitation BPJS Health claim process, there are obstacles that cause the submission of BPJS claims to be delayed and the disbursement of puskesmas funds taking a long time. From this background, the researcher wants to know how to submit BPJS claims at the Nanggulan Health Center. Objective to knowing how to submit BPJS claims at the Nanggulan Health Center. Methods is to Descriptive research with a qualitative approach. Results this research is submission of non-capitation BPJS Health claims using SOPs based on the MoU. The P-Care application also plays a role because there must be a print out of P-Care which is a requirement for submitting a claim. There are obstacles found at the Nanggulan Health Center, namely claims made only for delivery claims, this is due to the lack of human resources for claims officers, incomplete files are still found, and bridging failures often occur between SIMPUS and P-Care applications which affect P-Care print outs. The submission of non-capitation BPJS Health claims at the Nanggulan Health Center has been going well but problems are still found in the completeness of the non-capitation claim files, claims made are only claims for childbirth, and SIMPUS is often not bridging with P-Care.